2006
DOI: 10.1007/s11207-006-0265-4
|View full text |Cite
|
Sign up to set email alerts
|

Sunspots with the Strongest Magnetic Fields

Abstract: Abstract. The strongest observed solar magnetic fields are found in sunspot umbrae and associated light bridges. We investigate systematic measurements of approximately 32 000 sunspot groups observed from 1917 through 2004 using data from Mt. Wilson, Potsdam, Rome and Crimea observatories. Isolated observations from other observatories are also included. Corrections to Mt. Wilson measurements are required and applied. We found 55 groups (0.2%) with at least one sunspot with one magnetic field measurement of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
3
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 34 publications
4
106
3
6
Order By: Relevance
“…However, it appears that one needs to introduce an Evershed flow to eliminate the apparent umbral bright ring in the continuum. Similar work on return-flux sunspot models was undertaken by Osherovich and Lawrence (1983), Osherovich and Garcia (1989), and Liu and Song (1996).…”
Section: Self-similar Fieldsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, it appears that one needs to introduce an Evershed flow to eliminate the apparent umbral bright ring in the continuum. Similar work on return-flux sunspot models was undertaken by Osherovich and Lawrence (1983), Osherovich and Garcia (1989), and Liu and Song (1996).…”
Section: Self-similar Fieldsmentioning
confidence: 85%
“…Ringnes and Jensen, 1960;Brants and Zwaan, 1982;Kopp and Rabin, 1992;Collados et al, 1994;Livingston, 2002;. The field strength drops steadily toward the sunspot's periphery, becoming 700 -1000 G at the edge of the visible sunspot (e.g.…”
Section: Field Strength and Orientationmentioning
confidence: 98%
“…Typically, magnetic field strengths of about 1 kG are found in penumbrae while the maximum umbral field strengths usually range between 2 and 4 kG (Title et al 1993;Lites et al 1993;Schad 2013). In extreme cases, values as large as 6 kG have been reported (Livingston et al 2006). Only recently, van Noort et al (2013) reported ≈7 kG in a sunspot, although surprisingly not in the umbral area but near the outer edge of the penumbra, in a strong downflow region.…”
Section: Temporal Evolution Of the Magnetic Fieldmentioning
confidence: 99%
“…Livingston et al (2006), who searched historical measurements from Mt Wilson and Rome observatories covering many decades for spots with particularly strong fields, found that only 0.2% of all spots have field strengths larger than 4 kG, with the strongest umbral field ever measured being 6.1 kG. The values in excess of 7 kG measured in the downflows would therefore make these candidates for the strongest fields ever measured on the Sun.…”
Section: Strong Magnetic Fieldsmentioning
confidence: 99%